New fruit waste-derived activated carbons of high adsorption performance towards metal, metalloid, and polymer species in multicomponent systems - Sylwia Kukowska; Piotr Nowicki; Katarzyna Szewczuk-Karpisz (Scientific Reports)
Abstract The main aim of the study was to develop new fruit waste-derived activated carbons of high adsorption performance towards metals, metalloids, and polymers by the use of carbon dioxide (CO2)-consuming, microwave-assisted activation. The authors compared morphology, surface chemistry, textural parameters, and elemental composition of precursors (chokeberry seeds, black currant seeds, orange peels), as well as biochars (BCs) and activated carbons (ACs) obtained from them. The adsorption mechanisms of metals (copper, cadmium), metalloids (arsenic, selenium), and macromolecular compounds (bacterial exopolysaccharide, ionic polyacrylamides) on the surface of selected materials were investigated in one- and two-component systems. Consequently, the capacities of BCs and ACs prepared through direct/indirect physical activation, using conventional/microwave heating were determined. It was noted that microwave heating favoured surface development and thus enhanced adsorbent ability to bind ions or macromolecules. Direct biomass activation led to higher microporosity compared to indirect (two-stage) one, whilst CO2-consuming activation increased aromaticity and hydrophobicity of the solids. In the two-component systems, polymers could favour metal/metalloid adsorption based on complexation phenomena. However, the most efficient and environmentally safe activated carbon turned out to be the one obtained from orange peels by microwave-assisted, direct activation at 800 °C in the CO2 atmosphere.